2022
DOI: 10.29333/ejecs/942
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mathematics Achievement: An Analysis of Fourth and Eighth Grade TIMSS U.S. Data by Ethnicity, Gender, and Sociocultural Variables

Abstract: Previous research studies about mathematics performance have continuously reported race/ethnic or gender gaps. Learners have different educational experiences depending on not only their ethnicity or gender, but also grade and sociocultural factors. However, only a few studies have considered all these factors integrally. Hence, the need of examining academic performance differences across ethnicity, gender, grade, and sociocultural variables led this study. The purpose of this study was to examine mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…For instance, findings revealed that teachers from both countries could not successfully use educational technology due to the inadequacy of computers and/or tablets, lack of technical support, long waiting periods for technical support, and lack of continuous professional development. Similar to previous research [46][47][48], all the participants explained that the lack of support, in particular, technical support, hindered the use of educational technology in mathematics instruction. None of the German participants mentioned internet connection as a barrier to the integration of educational technology.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For instance, findings revealed that teachers from both countries could not successfully use educational technology due to the inadequacy of computers and/or tablets, lack of technical support, long waiting periods for technical support, and lack of continuous professional development. Similar to previous research [46][47][48], all the participants explained that the lack of support, in particular, technical support, hindered the use of educational technology in mathematics instruction. None of the German participants mentioned internet connection as a barrier to the integration of educational technology.…”
Section: Discussionsupporting
confidence: 69%
“…Secondly, the full model (for each country) containing school-and learner-level predictors was created to determine the association between the use of educational technology and the mathematics achievement of learners (see Table 3). Gender and SES were included in the model to control for; this is typically done in model building, as much research has shown that gender [46,47] and SES [48][49][50] are significantly associated with learner achievement, and our aim is to investigate educational technology use in a comparative study between South African and German schools (and not to investigate gender and SES associations with learner achievement); thus, there was a need to control for gender and SES. The variance at Level-2/school-level is 2978.82 and 550.83 for South Africa and Germany, respectively, which represents 2978.82/(2978.82 + 5029.82) × 100 = 37.2% (South Africa) and 550.83/(550.83 + 3523.93) × 100 = 13.5% (Germany) of the total variance per country.…”
mentioning
confidence: 99%
“…Consistent correlations between e-textbook features and teaching practices were also observed in the TIMSS 2019 study and its associated video analysis (Bokhove, 2022). A TIMSS analysis of U.S. eighth-grade data demonstrated a positive correlation between the number of topics covered in a textbook and the instructional time allocated (Moon, 2020) E-textbooks dictate the topics covered in mathematics lessons and in uence their presentation and perceived importance (Yerushalmy, 2015). They are a crucial component in distance education, with most classroom and homework exercises derived from these resources (Simonson et al, 2019).…”
Section: Literature Reviewsupporting
confidence: 54%
“…Finally, this study provides support for the notion that parental involvement plays a significant role in student's academic achievement, regardless of grade level and ethnicity. The findings suggest that when parents are actively engaged in their children's education, it positively impacts their academic performance (Moon et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%